INOVASI MANAJEMEN EVENT PT MARKPLUS INDONESIA DALAM MENGADAKAN EVENT ONLINE DI MASA PANDEMI - Sadra Khalita Binardi (2022)
The This study aims to determine the process and form of innovation carried out by PT markplus Indonesia in changing the organization of offline events to online events during the pandemic and to find out the innovation process, forms and obstacles faced in innovating while running online events during the pandemic. This study uses the theory of diffusion of innovation to discuss the decision to innovate made by PT Markplus Indonesia. This research uses qualitative research with a case study approach. The data collection technique used in-depth interviews with five informants and focused observations. The data analysis technique used by the researcher is a data analysis technique which consists of three stages, namely data reduction, data display, and conclusions and data verification. The results of this study found that PT Markplus Indonesia experienced changes in manpower and the delivery event process. PT Markplus Indonesia uses new media as their communication media, through Zoom Meeting and YouTube Live. The online event that has been carried out through the system is a novelty for PT Markplus Indonesia which makes the company's financial statements stable and presents many online events that are present.